(untitled) (Herald of Journalism, 2020)
The propaganda of the achievements of science is framed in special forms and carried out by profes- sional media in collaboration with the scientific community. The appeal to the mass audience of scien- tific material can be seen at the level of submission of the analysis of scientific information. The purpose of this article is to analyze the components of discussion in the context of the repre- sentation of science in a social scientific environment. The author explains the weakness of analytical components with the simplification of content in the information consumption market. The scientific and practical value of the study is to establish the degree of dependence of scientific and educational activities on the level of integration of mass communication and scientific journalism. In the course of the analysis of this topic, along with empirical methods such as description, control and comparison, systematization and study of documents, sociometric methods, theoretical axiomatic approaches based on research by foreign scientists were also used. The main results of a scientific article are: an analysis of the importance of scientific and educational activities for the development of the state and meeting the needs of society; recommendations on the development of mechanisms to stimulate research and increase the status of a scientist. The value of the article. The author claims that for the development of scientific journalism pro- paganda of scientific information alone is not enough. And he comes to the conclusion that scientific innovations and publications should be submitted through the tools of scientific communication, taking into account the characteristics of the audience.